Implementasi Model Pembelajaran Edutainment dalam Pengembangan Kreativitas Belajar Siswa Mata Pelajaran PAI di Kelas VIII SMPN 35 Surabaya - Lilis Sa’adah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
This study aims as: 1. To find out how the edutainment learning model is, 2. To find out how the implementation of the edutainment learning model for PAI subjects in class VIII SMPN 35 Surabaya, 3. To find out how the development of PAI students' learning creativity using the edutainment learning model in class VIII class SMPN 35 Surabaya. In this study, researchers used descriptive qualitative research. Because this research focuses on the application process